2020
DOI: 10.1371/journal.pone.0229934
|View full text |Cite
|
Sign up to set email alerts
|

The role of phonology in lexical access in teenagers with a history of dyslexia

Abstract: We examined phonological recoding during silent sentence reading in teenagers with a history of dyslexia and their typically developing peers. Two experiments are reported in which participants' eye movements were recorded as they read sentences containing correctly spelled words (e.g., church), pseudohomophones (e.g., cherch), and spelling controls (e.g., charch). In Experiment 1 we examined foveal processing of the target word/nonword stimuli, and in Experiment 2 we examined parafoveal pre-processing. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…Whilst it is widely recognised that children rely on phonological decoding in the early stages of learning to read, current theories do not fully account for skilled readers’ pre-lexical processing of phonology, that is, phonological recoding [5,6,7,8,9,10], with only one recent model of word recognition seeming to account for this developmental transition (the multiple-route model; [59]). Eye movement research has shown pre-lexical processing of phonology in typically developing readers from the age of 7 years through to skilled adult readers, as well as in atypical developmental groups, despite the tasks used not requiring any overt phonological processing [14,35,39,43,53,54]. Thus, eye movement research provides compelling evidence for phonology having a continued and pervasive role in facilitating lexical identification during reading (consistent with the multiple-route model; [59]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whilst it is widely recognised that children rely on phonological decoding in the early stages of learning to read, current theories do not fully account for skilled readers’ pre-lexical processing of phonology, that is, phonological recoding [5,6,7,8,9,10], with only one recent model of word recognition seeming to account for this developmental transition (the multiple-route model; [59]). Eye movement research has shown pre-lexical processing of phonology in typically developing readers from the age of 7 years through to skilled adult readers, as well as in atypical developmental groups, despite the tasks used not requiring any overt phonological processing [14,35,39,43,53,54]. Thus, eye movement research provides compelling evidence for phonology having a continued and pervasive role in facilitating lexical identification during reading (consistent with the multiple-route model; [59]).…”
Section: Discussionmentioning
confidence: 99%
“…Atypical development. Most recently, studies have begun to show evidence for pre-lexical phonological processing in populations with atypical reading development, specifically in individuals with permanent childhood hearing loss (PCHL; [53]) and individuals with developmental dyslexia [54]. Both of these participant populations are known to commonly experience substantial difficulties in learning to read, and one component of these difficulties is thought to be poor phonological processing skills, e.g., [55,56,57].…”
Section: The Role Of Phonology: Eye Movement Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to these studies, we used a method of silent reading, in which participants are not required to pronounce words or explicitly decide upon their lexical status. Such a paradigm allows the exploration of cognitive processes underlying reading without extraneous task demands, and according to some authors, it is better suited for research on visual word recognition (Bermúdez-Margaretto et al, 2020a; Blythe et al, 2020). We manipulated the word form frequency (high vs. low) and the correct spelling (correct words vs. words with error) of the written words in the silent word reading ERP task to test the following hypotheses: (1) word frequency influences error recognition; and (2) the time course of real error recognition is similar to pseudohomophone recognition, but due to the orthographic similarity with correctly written words, it can have its own characteristics.…”
Section: Introductionmentioning
confidence: 99%